MR enhancement of the internal auditory canal induced by tissue implant after resection of acoustic neurinoma. - Kremer, Paul; Forsting, Michael; Hamer, Jürgen; Sartor, Klaus (American journal of neuroradiology, 1998)
PURPOSE We studied intrameatal changes in MR enhancement induced by free-tissue implant over time after surgery for acoustic neurinoma. - METHODS Twenty-one patients were examined by MR imaging after suboccipital resection of an acoustic neurinoma. Precontrast and postcontrast MR images were obtained within 3 days after surgery (early MR images), then 6 weeks (intermediate MR images) and 6 months (late MR images) after surgery. A muscle graft as a free-tissue implant was used within the internal auditory canal in 18 of the 21 patients to seal pneumatic cells of the petrosal bone inadvertently opened and to prevent leakage of cerebrospinal fluid. - RESULTS On the early MR images, only minimal leptomeningeal or perineural enhancement was seen in 16 patients. There was no sign of residual tumor; however, enhancement increased and changed from linear to nodular on the intermediate MR images in 16 of the 18 cases in which a muscle graft had been used during surgery, mimicking a small intrameatal tumor. This nodular enhancement was still visible on the late MR images in 13 of the 16 cases. - CONCLUSION Nodular MR enhancement within the internal auditory canal a few weeks to months after surgery for acoustic neurinoma may be induced by packing material and should be considered when interpreting postoperative MR images.
Gesehen am 16.07.2025